The role of country by country reporting on corporate tax avoidance: does it effective for the tax haven? - Kurniasih, Lulus; Yusri, Yusniyati; Kamarudin, Fakarudin; Sheikh Hassan, Ahmad Fahmi (Taylor and Francis, 2022)
The study evaluates the direct and moderating influence of Country-by-Country Reporting (CbCR) regulation in deterring corporate tax avoidance of multi-national corporation listed in Indonesia Stock Exchange. The Indonesian CbCRstated in the regulations enacted by government of Indonesia namely Ministry ofFinance Regulation no. 213/PMK/2016 (MoFR 213/PMK/2016) and DirectorateGeneral of Taxes Regulation no. 29/2017 (DGTR-29/2017). We use panel data in thisstudy. Data is collected from the financial statements of 166 multinational com-panies listed in Indonesia Stock Exchange from 2010 to 2019, resulting in finalsample of 1315 observations. Pooled OLS regression is used to test the hypotheses.The results show that the CbCR regulation issued by the government has significantnegative impact on corporate tax avoidance measured by abnormal related partytransaction. Thus, it effectively deterred multinational companies’ corporate taxavoidance. Furthermore, we examine the influence of tax haven affiliation oncorporate tax avoidance which provides evidence that companies with tax havenaffiliation have higher level of corporate tax avoidance. However, the regulation isnot significant in moderating the relationship between tax haven affiliation andcorporate tax avoidance. The finding gives necessary information for policymakers to formulate a specific policy for the companies that own tax haven affiliation inorder to prevent profit shifting by practicing dysfunctional intra-company transac-tion. Furthermore, this study enriches the literature on the importance of govern-ment regulation as external monitoring tool that support tax avoidance theory.